Alcohol Extract of YFXJ Decoction Reverses the Drug Resistance of Human Lung Adenocarcinoma Cell Line A549/DDP. (21st July 2022) - Liu, Zhongliang; Ding, Yaping; Tian, Yizhou; Yu, Da
Abstract : Objective. Lung cancer is the wide and common tumor. This study was designed to explore the effect of YFXJ formula on non-small-cell lung cancer (NSCLC) cell lines. Methods. YFXJ formula (mainly composed of Astragalus membranaceus, Atractylodes macrocephala, Radix Saposhnikoviae, Radix Glehniae, coix seed, Herba Sabina chinensis, Hedyotis diffusa, Pericarpium Citri Reticulatae, sarcophagus martensii, Prunella vulgaris, Meretrix meretrix, and oyster) was extracted with 75% ethanol. We performed MTT, FACS, TUNEL, and mass spectrometry to study the effect of YFXJ formula on A549/DDP cells. Results. The results showed that YFXJ could inhibit the growth of A549/DDP cells, and it can reverse the sensitivity of A549/DDP cells to cisplatin. YFXJ inhibits the expression of MDR1, MRP1, and LRP genes in A549/DDP cells. Conclusion. YFXJ formula can reverse the drug resistance of A549/DDP cell, which could be through activation of autophagy.